Boards & spreads : shareable, simple arrangements for every meal - Fahr, Yasmin (Clarkson Potter/Publishers, 2022)
Provides more than sixty-five recipes for creating epic spreads for family-friendly, sharing meals that go beyond the standard cheese or charcuterie board and include Italian aperitivo board with crispy prosciutto caprese, any-night tacos, and egg pita sandwich board.